Security Vulnerabilities in Next Generation Air Transportation System - Atanasov, Atanas; Chenane, Ramillo (My University, 2014)
The thesis highlights the importance of Next Generation Air Transportation System (NextGen) as the demand for air transportation has drastically increased over the past few years. NextGen will require a number of changes to the current aviation infrastructure in the United States in order to make it more reliable, environmental friendly, efficient, and technologically advanced. The aviation community would benefit tremendously from NextGen because pilots and Air Traffic Control (ATC) towers will collect data and information in a way not supported by the previously used radar technology. This thesis points out the security vulnerabilities of Automatic Dependent Surveillance-Broadcast (ADS-B) protocol, which is a vital component for safety of air traffic. Through our research we have elaborated that both active and passive attacks are possible for a sophisticated attacker. Since the current proposed framework poses major security challenges thereby jeopardizing the performance of the future airspace system, we have developed a TVA matrix in order to highlight these concerns. We have studied an abundance of literature from highly ranked security publications in government, industry, and academia on NextGen and ADS-B in order to provide a holistic overview of the security risks and to allow the reader to develop an understanding of such vulnerabilities. In addition, we have proposed additional attacks and mitigation techniques, which we believe have been overlooked in the literature. To the best of our knowledge the Threats, Vulnerabilities, and Attacks (TVA) matrix developed in this thesis provides a summary of malevolent (e.g. spoofing) data in a unique way never possible before. Even though we have focused on a particular technology, the techniques (e.g. TVA matrix, mitigation) covered here are flexible and can be applied to future technological advancements.
Keywords: Data- och informationsvetenskap; Computer and Information Science